A tactile graphic book with Braille and audio use improved plaque score and toothbrushing performance in visually impaired individuals - PinKwan P. (2023)
Objective: To evaluate the effectiveness of embossed tactile graphic books and Braille with an audio file for oral health education for visually impaired individuals. Materials and Methods: Forty visually impaired individuals (9–16 years old) were matched and randomly assigned into two groups. The education was provided using an audio file and practicing toothbrushing with teachers’ hands-on assistance for the audio/hands-on (A/HO) group and the tactile graphic book with audio and teacher supervision (ATB/TS) group. The oral health instruction was performed three times, once a week every 2 weeks, transitioning to a self-study session based on the group's method once a week for 4 weeks. Plaque score, brushing performance, and oral health knowledge were evaluated. Statistical analysis was performed using the Mann–Whitney U and Friedman post hoc test. Results: A significant improvement was found in both groups at week 6 of the intervention. However, the ATB/TS group had a significantly higher score than the A/HO group in the task analysis of tooth brushing step score (p-value < 0.001), PHP score (p-value = 0.001), and oral hygiene knowledge score (p-value < 0.001). Conclusion: Tactile graphic books and Braille with an audio file is an effective medium for the oral health education of visually impaired individuals.